Dietetic fiber in 22 children from the Hospital Infantil Club Noel of Cali, Colombia. (Colombia Medica, 2006)
Introduction: Functional chronic constipation is an important cause of consultation in pediatric gastroenterology. The role of the dietetic fiber in children is controversial as a cause of the constipation. Objective: To report the dietetic fiber consumption in 22 children of the Hospital Infantil Club Noel (HICN) of Cali. Report of cases: Were included 22 children (3-13 years), both gender, from the HICN of Cali with digestive diagnoses for the first time. A medical clinical history was made, and one interviews nutritional by reminder of 24 hours. Acute undernourishment was defined when the deficit for weight/height (W/H) was >10% and overweight when the excess for W/H was >10%. The chemical analysis of the dietetic fiber was made following the Content of Dietetic Fiber and Resistant Starch in Foods and Latin American Products of the CYTED. The patients were divided according to gender, intestinal habit, signs and symptoms; in children with constipation (n=9) and without constipation (n=13) (p=0.865, 95% IC -6.71 to 7.91). Conclusion: The 22 children of the HICN of Cali, independent of the constipation presence, consume 12.8±7.8 grams of dietetic fiber to the day, an amount that is the recommended one by almost all of the consulted studies.